Face Masks in Young Children During the COVID-19 Pandemic: Parents' and Pediatricians' Point of View - Rémy Assathiany; Catherine Salinier; Stéphane Béchet; Claire Dolard; Fabienne Kochert; Alain Bocquet; Corinne Levy; Corinne Levy; Corinne Levy; Corinne Levy (Frontiers Media S.A., 2021)
Background: In countries with high SARS-CoV-2 circulation, the pandemic has presented many challenges on different fronts, affecting lives and livelihoods; efforts to keep schools open are among the most important. In France, to keep schools open, wearing a face mask has been mandatory for children from age 6 years since November 2020.Objective: To evaluate the acceptability and tolerance of this measure by children as well as both parents and pediatricians.Setting: Parents registered on the website of the French Association of Ambulatory Pediatrics and pediatricians members of this association.Participants: All parents and pediatricians who agreed to take part in the survey.Results: Among the 2,954 questionnaires for the parents' survey, the reasons for wearing a mask were understood by 54.6% of parents, most of whom (84.6%) explained the reasons to their children. The parents applied this measure because it was mandatory (93.4%) even if they disagreed (63.3%). When interviewed by parents, children said they were usually embarrassed (80.9%) by the mask. The main symptoms or changes of behavior attributed to the mask according to parents were headache (49.0%), speaking difficulties (45%), change in mood (45.2%) and breathing discomfort (28.1%). Among the 663 pediatricians who responded, many agreed with mandatory mask-wearing at age 6 years (67.7%). Overall, 15% of pediatricians systematically asked about the mask tolerance during the consultation. During the medical consultation, when the parents complained about the mask (64.3%), the main drawbacks were related to fog on glasses (reported by 68.2% of pediatricians), breathing discomfort (53.1% of pediatricians), cutaneous disorders (42.4% of pediatricians) and headaches (38.2% of pediatricians).Conclusion: Despite the many inconveniences reported, children agree to wear the mask better than their parents think. Pediatricians should sufficiently take the opportunity during the consultation to further explain the reasons for wearing the mask because their pedagogical role is crucial.